The utilization of Instagram social media on @kalis.mardiasih accounts as a means of campaign regarding gender equality in Women - Mawadda, Safira; Anisa Sari, Eka (Universitas Ahmad Dahlan, 2024)
The research entitled The Utilization of Instagram Social Media on @kalis.mardiasih accounts as a Means of Campaign Regarding Gender Equality in Women uses campaign theory using the Campaign Component Model. This study aims to find out the use of Instagram @kalismardiasih with several parts, namely campaign actors, campaign messages, campaign media channels, campaign effects, campaign feedback, and campaign disruptions that occur on Instagram accounts @kalismardiasih related to campaigns carried out regarding Gender Equality. Research on gender equality in the modern era is essential because it helps to understand the problems of gender inequality that continue to arise in society and drives social change towards justice and equality for all genders in various aspects of life. The research uses a descriptive qualitative method with data collection techniques using unstructured interviews, observations, and documentation. The results of this study found that in the Instagram account, @kalismardiasih, used as a campaign media related to the issue of feminism, one of which is gender equality, the campaign message on Instagram is packaged attractively and diversely so that it is easier to digest. In contrast, the campaign channel utilizes various Instagram features. The campaign's success raised awareness about the importance of gender equality in women, with feedback that many women said and felt represented by the campaign on the @kalismardiasih account; there was rejection and criticism from those who disagreed with the campaign she was doing.